2021
DOI: 10.1002/ehf2.13586
|View full text |Cite
|
Sign up to set email alerts
|

Extended follow‐up after wearable cardioverter‐defibrillator period: the PROLONG‐II study

Abstract: Aim The wearable cardioverter‐defibrillator (WCD) is used for temporary protection from sudden cardiac death (SCD) in patients with newly diagnosed heart failure with reduced ejection fraction before considering an implantable cardioverter‐defibrillator (ICD). However, the prognostic significance of the WCD remains controversial due to conflicting evidence. The aim of the present study was to evaluate prognosis of patients receiving life‐saving WCD shocks. Methods and results All patients receiving a WCD at Ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…We and others have previously argued that a prolonged time should be taken for therapy optimization and risk stratification before deciding on ICD implantation [13][14][15]. The PROLONG and PROLONG-II study have suggested that ICD implantations can be avoided in some patients with newly diagnosed HFrEF by this practice without increasing the risk of sudden cardiac death [13,23]. The present analysis was conducted to evaluate which patients benefit from an extended waiting period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We and others have previously argued that a prolonged time should be taken for therapy optimization and risk stratification before deciding on ICD implantation [13][14][15]. The PROLONG and PROLONG-II study have suggested that ICD implantations can be avoided in some patients with newly diagnosed HFrEF by this practice without increasing the risk of sudden cardiac death [13,23]. The present analysis was conducted to evaluate which patients benefit from an extended waiting period.…”
Section: Discussionmentioning
confidence: 99%
“…The PROLONG-II study was an observational single-center study evaluating the prognosis of patients with HFrEF after WCD prescription. Detailed trial design has been described elsewhere [23]. In brief, patients receiving a WCD (LifeVest, Zoll, Pittsburgh, PA, USA) for newly diagnosed HFrEF at Hannover Medical School between 2012 and 2017 were included.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PROLONG-II study enrolled patients who received a WCD (LifeVest, ZOLL, Pittsburgh, PA, USA) at Hannover Medical School [ 18 ]. The aim of the present study was to provide extended follow-up after WCD prescription.…”
Section: Methodsmentioning
confidence: 99%
“…The TRENDS data were captured and available also in clinical patients outside of clinical trials, while the visibility within the online network needs to be activated for each patient and each physician separately and is not routinely used for follow-ups. Recently, a retrospective analysis of TRENDS data patients from the PROLONG II trial [ 52 ] proposed a clinical application of the TRENDS data: 267 patients (31.9% female, mean LVEF 25.3 ± 8.5%) with a newly diagnosed CMP were observed over the time of WCD prescription (111.8 ± 74.5 days). The first and last seven days of usage were compared and showed significant changes in heart rate, step count, and five-minute heart rate variability approximate (HRV5), which is a surrogate for beat-to-beat heart rate variability and was calculated from the data available from the online network.…”
Section: Multiparameter Monitoringmentioning
confidence: 99%